Enhancement of Low-Quality Images using Bi-Histogram Equalization adaptive sigmoid function based on Shifted Gomphertz Distribution - Sandeep; Suresha, M (International Journal of Computer Sciences and Engineering, 2019)
Image enhancement participate crucial role in image processing area and its main agenda is improves visual quality of an image. Histogram equalization is most prevalent method in contrast enhancement. But its major drawback is overenhancement, therefore, it generates abnormal appearance. In this paper, proposed a method that solve over brightness problem by separate two histograms based on mean values of V-channel or intensity channel of HSV image. To calculate cumulative density function for each sub-histogram with two sigmoid function with their origins placed on the medians of sub-histogram after Shifted Gomphertz Distribution applied for each sub-histogram and equalized independently using histogram equalization. Experimental results demonstrate that proposed method gives good results compare to other state-of-the-arts methods with respect to over-enhancement.